ANALISIS PEMBIAYAAN NON-ANGGARAN PEMERINTAH DALAM MENDUKUNG PEMBANGUNAN INFRASTRUKTUR DI INDONESIA - Nanda Cahyani Putri; Loveani Yastika Putri (Jurnal Infrastruktur, 2020)
Infrastructure is one of the national development priorities in the National Medium-Term Development Plan (RPJMN) 2020-2024 as infrastructure development aimed to improve the economic condition and provide basic services. One of the challenges of providing good-quality infrastructure is the need for a huge amount of budget while the government's financial capacity is very limited. Accordingly, developing sufficient infrastructure across the country has become a crucial problem for central, regional, and local governments. The government is, therefore, should create innovation for the infrastructure financing mechanism by using the non-government budgeting scheme. This study aims to analyze the scheme of non-government budgeting that is suitable in Indonesia. The analysis uses a scoring method based on criteria compiled from the literature. Interviews with relevant stakeholders were applied to examining the scoring analysis. The result shows that there are four potential schemes to be developed in Indonesia, which are land consolidation, loans, bonds, and Public-Private Partnership (PPP).